Turn the tide on losing members to cults: The challenge of the churches in the Congo - Mufika, Mathieu B.; Stoker, Hendrik G. (In die Skriflig / In Luce Verbi, 2020)
Especially since the late 20th century, former ‘Western’ cults such as the Jehovah Witnesses, Mormons and Branhamites, became a real threat to churches in the greater Kolwezi, the rest of the Democratic Republic of Congo (DRC) and several other places in Africa. Because these cultic groups question some of the most basic teachings of Christianity, including who God is and whether salvation occurs through Jesus Christ alone, it is crucial for Christian churches confronted with them, to respond apologetically in an effective way. To be able to do it, it is important to understand why these groups made such inroads and proselytes from Christian churches. In the article such background is given and a way forward through Christian apologetics and a missionary strategy is discussed.
free